Cadmium sulfide quantum dots stabilized by aromatic amino acids for visible light-induced photocatalytic degradation of organic dyes. (24th September 2015) - Zhang, Jie; Guo, Yuming; Fang, Hui; Jia, Weili; Li, Han; Yang, Lin; Wang, Kui
<x xml:space="preserve">Abstract</x> CdS QDs stabilized by aromatic amino acids photocatalytically degrade organic dyes under visible light irradiation through mediation of hydroxyl radicals.